Bioactive lipids and metabolic syndrome—a symposium report. Issue 1 (25th February 2022) - DeVito, Loren M.; Dennis, Edward A.; Kahn, Barbara B.; Shulman, Gerald I.; Witztum, Joseph L.; Sadhu, Sudeshna; Nickels, Joseph; Spite, Matthew; Smyth, Susan; Spiegel, Sarah
Abstract: Recent research has shed light on the cellular and molecular functions of bioactive lipids that go far beyond what was known about their role as dietary lipids. Bioactive lipids regulate inflammation and its resolution as signaling molecules. Genetic studies have identified key factors that can increase the risk of cardiovascular diseases and metabolic syndrome through their effects on lipogenesis. Lipid scientists have explored how these signaling pathways affect lipid metabolism in the liver, adipose tissue, and macrophages by utilizing a variety of techniques in both humans and animal models, including novel lipidomics approaches and molecular dynamics models. Dissecting out these lipid pathways can help identify mechanisms that can be targeted to prevent or treat cardiometabolic conditions. Continued investigation of the multitude of functions mediated by bioactive lipids may reveal additional components of these pathways that can provide a greater understanding of metabolic homeostasis.